Study of prevalence of bacterial vaginosis in preterm and term labour patients - Shree, Tamanna; Kaur, Amrit Pal; Dhillon, S. P. S.; Oberoi, Loveena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Bacterial vaginosis (BV) is a clinical condition caused by replacement of the normal hydrogen peroxide producing Lactobacillus species with high concentrations of aerobic and anaerobic bacteria. Studies have shown that spontaneous abortion, preterm labour (PTL), premature birth, preterm premature rupture of membranes, amniotic fluid infection, and postpartum endometritis are increased because of infection with BV. In India, not many studies have been done to estimate the prevalence and association of BV with preterm labour, hence this study is being taken up to know the prevalence of BV in preterm and term labour patients and its relationship with preterm delivery, low birth weight of baby and puerperal sepsis.The objective of the present study was to observe the prevalence of bacterial vaginosis in women presenting with preterm and term labour, its impact on preterm and term delivery and to analyze the maternal and fetal complications associated with BV. Methods: An observational study involving 100 patients with preterm and term labour (50 patients in each group) was conducted at a BNMCCC, Government Medical College, Amritsar. Women fulfilling the Amsel’s criteria and/or a score of 7 or more on gram staining of vaginal smears (Nugent’s score) was considered to have bacterial vaginosis. Results: The proportion of patients, who fulfilled Amsel’s criteria and/or a Nugent’s score of 7 or more for the diagnosis of BV, was more in PTL group versus term labour group, and the difference was statistically significant. Prevalence of BV in preterm labour and term labour patients was 18(36%) versus 4(8%) respectively. In PTL group, 27.8% of low birth weight neonates were born to BV positive mothers versus 3.1% were born to BV negative mothers. Maternal postpartum complications observed were 33.3% with BV versus 6.25% without BV in PTL group. Conclusions: BV is major risk factor for PTL. Therefore, the testing and prompt treatment of BV may reduce the risk of PTL. This will also go a long way in the prevention of maternal morbidity and neonatal complications due to prematurity.